Autografting with CD34+ peripheral blood stem cells: retained engraftment capability and reduced tumour cell content - Voso, Maria Teresa; Hohaus, Stefan; Moos, Marion; Pförsich, Margit; Cremer, Friedrich Walter; Schlenk, Richard Friedrich; Martin, Simona; Hegenbart, Ute; Goldschmidt, Hartmut; Haas, Rainer (British journal of haematology, 1999)
The efficacy of an immunomagnetic purging method and the Isolex 300 devices were assessed for selecting CD34+ cells from leukapheresis products of 29 patients with non-Hodgkin's lymphoma (NHL), 39 with multiple myeloma and 34 with breast cancer. The mean purity of the CD34+ cell population was 93.6% and the mean recovery was 67.7%. Following enzymatic cleavage by chymopapain the expression of Thy-1 and Leu-8 was significantly reduced without affecting haematological recovery. The population of selected CD34+ cells of 4/8 patients with follicular lymphoma became PCR-negative. A 2.5 log reduction of tumour cells could be achieved in four patients with multiple myeloma as shown by a quantitative PCR assay. There were no tumour cells detectable in any of the 19 CD34+ cell preparations of patients with breast cancer. In 64 patients who received 94 cycles of high-dose therapy, a mean number of 4.7 × 106 CD34+ cells/kg were autografted. The time needed for platelet reconstitution was different when a comparison was made with 156 patients, who had received unmanipulated leukapheresis products (10 v 12 d, P = 0.006). No significant differences with regard to neutrophil recovery were noted. Five patients had a graft failure. Two of them died (on day 78 and 88 following PBSCT), and three patients were rescued with unmanipulated back-up transplants. In conclusion, the immunomagnetic selection of CD34+ cells provides autografts with reduced tumour cell content and an engraftment ability similar to that of unmanipulated autografts.
Elektronische Reproduktion der Druckausgabe
Gesehen am 01.03.2022